(untitled) (Journal of Human Sciences, 2021)
The research aimed to know the strategies for managing conflict between teachers by the principals of primary education school in the city of Sebha, And highlighting the concepts related to conflict management strategies and the extent of their application and ,success in the education sector, The two researchers used the descriptive analytical approach to know conflict management strategies, The research sample consisted of (120) teachers and information distributed over (7) schools, and the research tool included a questionnaire prepared by The two researchers, The search found : The most common strategy among school principals in management conflict is the settlement strategy, This is followed by the cooperation strategy, then the avoidance strategy, then the adaptation strategy, and finally force strategy, There are no statistically significant differences between the averages of the responses of the research sample to the exclusion of the questionnaire as a whole due to the gender variable. What is the strength strategy, There are differences between the responses of the sample members due to the gender variable in favor of females, There are statistically significant differences between the averages of the respondents’ responses to the deportation of the questionnaire due to the age variable, These differences are in favor of those under the age of(30) There are no statistically significant differences between the averages of the respondents’ responses about the deportation of the questionnaire due to the qualification variable, There are no statistically significant differences between the averages of the respondents’ responses regarding the exclusion of the questionnaire as a whole due to the variable years of experience.